New pectin derivatives with antimicrobial and emulsification properties via complexation with metal-terpyridines. (15th September 2021) - Hassan, Enas A.; Abou Elseoud, Wafaa S.; Abo-Elfadl, Mahmoud T.; Hassan, Mohammad L.
Abstract: Pectin is widely used in food and pharmaceutical industries. However, due to its polysaccharide nature it lacks antimicrobial activity. In the current work, new pectin derivatives with interesting optical and antimicrobial properties were prepared via supramolecular chemistry utilizing Fe- or Cu-terpyridine (Tpy-Fe and Tpy-Cu) motifs. To proof derivatization of pectin, ultraviolet-visible spectroscopy (UV–Vis) and Fourier Transform infrared (FTIR) were used. In addition, the prepared pectin derivatives retained the known emulsification activity of the non-modified sugar beet pectin as seen from the particle size analysis of oil-in-water emulsions. The prepared derivatives showed antibacterial activity toward selected Gram-positive and Gram-negative bacteria. In addition, cytotoxicity test showed that the Tpy-Fe-pectin derivative was non-toxic to cells of human hepatocarcinoma, breast adenocarcinoma MCF7, and colorectal carcinoma cells at concentrations up to 100 μg/ml, while Tpy-Cu-pectin had moderate toxicity toward the aforementioned cells at the same concentration levels. The prepared derivatives could have potential applications in emulsions with antibacterial activity. Highlights: New pectin derivatives were prepared using Cu II - and Fe II -terpyridine complexes. The terpyridine-pectin derivatives had good emulsification properties for O/W emulsions. The prepared terpyridine-pectin derivatives showed good antibacterial properties. Terpyridine-Cu-pectin derivative showed moderate cytotoxicity. Terpyridine-Fe-pectin derivative showed non-cytotoxicity.